DIGITAL LITERACY IMPLEMENTATION IN DESIGN ENGLISH LEARNING FOR ENGLISH TADRIS STUDENTS USING THE CANVA APPLICATION - Yashori Revola; Tri Nur Susanti (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
Learning media is needed to support and support the teaching and learning process in an education. Media is a tool that educators can use when learning in class. The creativity of educators in creating interesting and fun learning media must always be improved. Presentation of English material for the S-1 level of English Education must be provided in various forms of presentation that do not have to be tied only to textbooks, especially English material. An educator should have new and interesting learning media in delivering material to his students, not just through books or just the lecture method. Learning media used by educators must be adapted to the material and conditions of students. In today's era, technology is developing rapidly, every individual is expected to be able to take advantage of existing technology to support daily activities, including in education. Among the technological media that educators can use to learn to improve English mastery in first semester students of English is Canva. Canva is an online-based design application that lecturers can use to design learning materials through templates, posters, videos, infographics, and even presentation media. The many attractive designs in the Canva application can make it easier for lecturers to deliver learning material, students don't get bored easily and make learning fun and more effective. This research focused on the function of the Canva application as a learning medium that could be used by both educators and students. The purpose of this study was to find out more about the features in the Canva application that could be used to create learning media, with the hope of increasing innovation in designing interesting, effective and interactive learning media so that the planned learning targets were achieved. This research method used qualitative research methods, where data was collected through interviews and surveys through questionnaires. The results obtained were as much as 51% really understood, 20% understood, and 29% did not understand. Thus, the Canva application is feasible to be implemented in learning both offline and online to help facilitate understanding and increase the ability to master learning material.